Intellectual and educational potential of Kazakh proverbs and sayings (Journal of Philosophy Culture and Political Science, 2018)
In the article the subject of a special analysis becomes 15,848 proverbs, published in 65,66,68 volumes of the cultural heritage «Babalar sozi», implemented under the state program. Proverbs and sayings testify the enormous educational, enlightenment, personal-oriented potential of Kazakh folklore.Worldview, communicative, meaning of proverbs and sayings contributes to a creative , competitive personality, which is able to confrontthe globalization and the challenges of the modern civilization. Analyzing the principles of quality and publication of proverbs and sayings. In these volumes familiar proverbs and sayings are placed along with them there are some unknown proverbs are offered to the readers as well. Paying special attention to educational opportunites of proverbs and sayings. Specifically analyzing the theme of parents, motherland, nativeland, the upbringing of children, the succession of generations, a tolerant relationship, adaptation to work, the unity of physical and mental labor, education, science and intellingence.Key words: culture heritage, proverbs and sayings, worldview, intellectual capacity, creative person.